2022
DOI: 10.1002/cssc.202201616
|View full text |Cite
|
Sign up to set email alerts
|

Heptazine‐Based Ordered‐Distorted Copolymers with Enhanced Visible‐Light Absorption for Photocatalytic Hydrogen Production

Abstract: Poly(heptazine imide) (PHI), one of the attractive allotropes of polymeric carbon nitride, has recently received extensive attention in photocatalysis due to its extended conjugation for fast separation and transfer of the charges. However, pristine PHI bears an intrinsic optical absorption band edge at 460 nm, which largely restrains the visible light utilization. Herein, the narrow‐bandgap PHI (N‐PHI) with an ordered‐distorted interface was fabricated from polycondensation of the mixture of NaSCN, cyanuric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 72 publications
0
32
0
Order By: Relevance
“…13 However, the low exciton separation efficiency has hindered the photocatalytic HER activity of traditional carbon nitride materials. 14 To further improve the HER activity of carbon nitride, various genius strategies like precious metal modication, 15 defect engineering, 16 elemental doping, 17 molecular design, 18 morphology control, 19 and heterojunction construction 20,21 have been proposed and engaged in previous work. Among all the approaches mentioned above, morphology engineering for photocatalysts has been proven to be an effective method for increasing photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, the low exciton separation efficiency has hindered the photocatalytic HER activity of traditional carbon nitride materials. 14 To further improve the HER activity of carbon nitride, various genius strategies like precious metal modication, 15 defect engineering, 16 elemental doping, 17 molecular design, 18 morphology control, 19 and heterojunction construction 20,21 have been proposed and engaged in previous work. Among all the approaches mentioned above, morphology engineering for photocatalysts has been proven to be an effective method for increasing photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric carbon nitride (CN, also named melon) has received considerable attention due to its advantages of low production cost, non-toxicity, a suitable band gap (∼2.7 eV), and excellent thermal and chemical stability. Since Wang et al first reported the photocatalytic water splitting by CN in 2009, dramatic achievements have been realized in various photocatalytic applications of CN, such as biorefinery, , organic contaminant degradation, hydrogen peroxide generation, and CO 2 reduction. , However, CN, prepared by conventional thermal polycondensation methods, suffers from low crystallinity, insufficient utilization of visible light, and rapid recombination of charge carriers, resulting in poor photocatalytic efficiency. , To overcome these deficiencies, various modification strategies have been developed, including induction of active sites through heteroatom doping, construction of heterojunctions with other semiconductors or conductors, and nanostructure design. Among them, heteroatom (e.g., B, C, N, O, S, and P) doping was identified as an effective strategy for tuning the electronic properties of CN and improving its photocatalytic performance. ,,,, According to first-principles calculations, , nonmetal dopants should follow two principles: (i) the electronegativities of the nonmetal atoms must be lower than those of the substituted lattice atoms and (ii) the radius of the nonmetal atoms should be comparable to that of the substituted lattice atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraged by natural photosynthesis, the Z-scheme architecture combining a hydrogen production photocatalyst (HPP) and an oxygen production photocatalyst (OPP) using a suitable electron mediator has been proposed. , When exposed to light, the photogenerated holes in the HPP and electrons in the OPP migrate to the electron mediator for recombination, and the remaining electrons and holes undertake the redox reactions. The high-performance charge separation as well as favorable redox abilities of photoinduced carriers would be obtained in this Z-scheme configuration. , In addition, the separation of water redox sites can also inhibit the reverse reaction. , Due to the compact structure and higher photocatalytic performance, all-solid-state Z-scheme systems based upon solid-state electron mediators have attracted particular interest. To effectively accommodate photoinduced electrons in the OPP and holes in the HPP, the electron mediator needs to own high conductivity and appropriate work function. Meanwhile, to achieve a continuous flow of photogenerated carriers, a close contact between the mediator and different components should be constructed. , …”
Section: Introductionmentioning
confidence: 99%